2021
DOI: 10.1111/1541-4337.12781
|View full text |Cite
|
Sign up to set email alerts
|

Emerging nondestructive approaches for meat quality and safety evaluation—A review

Abstract: Meat is one of the most consumed agro‐products because it contains proteins, minerals, and essential vitamins, all of which play critical roles in the human diet and health. Meat is a perishable food product because of its high moisture content, and as such there are concerns about its quality, stability, and safety. There are two widely used methods for monitoring meat quality attributes: subjective sensory evaluation and chemical/instrumentation tests. However, these methods are labor‐intensive, time‐consumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 134 publications
0
22
0
2
Order By: Relevance
“…The results of most previous studies did not correspond significantly to the chemical or microbiological changes of the meat in some studies where sensory evaluation for meat quality evaluation was used, and the results found in most previous studies did not correspond significantly to the chemical or microbiological changes of the meat [2]. When using sensory evaluation to measure microbiological features, the inaccuracy can sometimes be too significant, resulting in a false positive or false negative.…”
Section: Sensory Evaluation Of Meatmentioning
confidence: 90%
See 4 more Smart Citations
“…The results of most previous studies did not correspond significantly to the chemical or microbiological changes of the meat in some studies where sensory evaluation for meat quality evaluation was used, and the results found in most previous studies did not correspond significantly to the chemical or microbiological changes of the meat [2]. When using sensory evaluation to measure microbiological features, the inaccuracy can sometimes be too significant, resulting in a false positive or false negative.…”
Section: Sensory Evaluation Of Meatmentioning
confidence: 90%
“…The demand for the use of nondestructive procedures in evaluating meat quality and safety qualities has increased due to the rapid rise in public knowledge and concern for superior meat quality [2]. According to the literature reviewed, the most sophisticated methods for evaluating meat quality that is based on imaging and the electromagnetic spectrum meet the demand criteria of being quick, nondestructive, and suitable for online/in-line monitoring.…”
Section: Recent Advanced Meat Evaluation Methods (Instrumental)mentioning
confidence: 99%
See 3 more Smart Citations